Role of Institutes of Political Dialogue in Republic of Kazakhstan - Andirzhanova, G. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
This article is about the role of institute of political dialogue in the context of preservation of stability in Kazakhstan. Keywords: Political Dialogue, social development, political system, basic institutes, nongovernmental organisations, democratization, political dialogue